ELASTIC RESISTANCE TRAINING AND ITS EFFECT ON THE VERTICAL DISTANCE, SOME BIO-KINEMATIC VARIABLES, AND THE PHYSICAL ABILITIES OF THE SHOOTING SKILL FROM JUMPING HIGH WITH HANDBALL - Lecturer. Dr. Amer Adnan Mezher (Galaxy International Interdisciplinary Research Journal, 2023)
The training of elastic resistances using rubber ropes and sandburst is one of the effective and important means in developing and developing the necessary physical abilities for handball players and what it achieves from a positive effect on the vertical distance of the jump and some biomechanical indicators required to perform the instantaneous push with one or both legs together at the highest technical, physical and mechanical level. This being the research problem that the researcher diagnosed in the field after studying the requirements of the shooting skill from jumping high with handball and the harmony and coordination needed for the work of the muscle groups working during the performance, which in turn helps the player to achieve the best mechanical position to reach the best possible vertical distance without slowing down in this Speed, and the research aims to identify the effect of flexible resistance training on the development of the vertical distance and some biokinematic variables and the physical capabilities of the shooting skill from jumping high with handball for the research group, and the researcher assumes that there are statistically significant differences between the pre and post measurements in the vertical distance, biokinematic variables and physical capabilities of the research sample, The researcher used the experimental method with one experimental group As for the research sample, it was from the advanced players in handball for Al-Nasiriyah Sports Club, if their number reached (10) players, who were chosen in the intentional manner. Internal strength, and thus reflected positively on the vertical distance at the moment of shooting, and the researcher recommended the use of other training methods to develop physical capabilities, biomechanical indicators, and shooting accuracy from jumping high according to the anatomical axes of movement.